2018
DOI: 10.1038/s41419-018-0434-z
|View full text |Cite
|
Sign up to set email alerts
|

TRIP13 promotes tumor growth and is associated with poor prognosis in colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common neoplasms worldwide. However, the mechanisms underlying its development are still poorly understood. Thyroid hormone Receptor Interactor 13 (TRIP13) is a key mitosis regulator, and recent evidence has shown that it is an oncogene. Here, we report that TRIP13, which is overexpressed in CRC, is correlated with the CEA (carcino-embryonic antigen), CA19-9 (carbohydrate antigen 19-9) and pTNM (pathologic primary tumor, lymph nodes, distant metastasis) classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…And these annotations were mainly related to the processes of cell proliferation and differentiation. Previous studies have demonstrated that TRIP13 promoted cell proliferation and invasion via interacting with YWHAQ and YWHAZ in CRC [10]. And TRIP13 mutations predispose to chromosome missegregation and tumorigenesis [8].…”
Section: Disscussionmentioning
confidence: 99%
See 3 more Smart Citations
“…And these annotations were mainly related to the processes of cell proliferation and differentiation. Previous studies have demonstrated that TRIP13 promoted cell proliferation and invasion via interacting with YWHAQ and YWHAZ in CRC [10]. And TRIP13 mutations predispose to chromosome missegregation and tumorigenesis [8].…”
Section: Disscussionmentioning
confidence: 99%
“…plays an oncogenic role in multiple human cancers and usually associated with poor survival [9,10,22,23]. Here, we determined to explore the role of TRIP13 in BC.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the majority of these interactions involved genes that had been demonstrated to play critical roles in cancer, such as TRIP13, MDFI, SPRY2 and MEOX2. Particularly, TRIP13 was found to promote cell proliferation, invasion and migration in cancer (34). In addition, MEOX2 was identified as a target gene of the TGF-beta/Smad pathway and was known to regulate cell proliferation (35).…”
Section: E-mutpath Identifies Informative Paths To Distinguish Diseasementioning
confidence: 99%